Can Inflation be Claimed As A Monetary Phenomenon? The Malaysian Experience - TANG, Chor Foon; Ozturk, Ilhan (International Journal of Economics and Financial Issues, 2017)
The purpose of this study is to empirically re-investigate the money-prices nexus for Malaysia through the cointegration and causality techniques. This study covered the monthly data from 1971:M1 to 2014:M8. The Maki multiple breaks cointegration test suggests that the variables are cointegrated. Furthermore, the MWALD test shows a unidirectional causal relationship run from money supply (M2) to aggregate prices, meaning that only the monetarist's view exist in the Malaysian economy. However, the time-varying causality tests indicate that inflation is not always a monetary phenomenon in Malaysia. Therefore, the contractionary monetary policy may not an effective instrument in managing inflationary behaviour in Malaysia. Keywords: Cointegration; Inflation; Money; Recursive regression; Rolling regression JEL Classifications: C22; E31; E51